Evidence-based CBT for anxiety and depression in children and adolescents : a competencies-based approach - Sburlati, Elizabeth S. (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2014)
'Evidence-Based CBT is the first book to take an explicitly competencies-based approach to the cognitive-behavioural treatment of anxiety and depression in children and young people. It draws on top-name expertise to define and demonstrate the therapist competencies needed to effectively implement CBT'--
'Covers a range of essential competencies including building a positive therapeutic relationship, case formulation, managing negative thoughts, changing maladaptive behaviours and modifying the family environment'--
An introduction to the competencies-based approach -- Effective training methods -- Generic therapeutic competencies -- Self-assessment of our competence as therapists -- Professional evidence-based practice with children and adolescents -- Child and adolescent characteristics that impact on therapy -- Building a positive therapeutic relationship with the child or adolescent and parent -- Assessing child and adolescent internalizing disorders -- CBT competencies -- Theoretical foundations of CBT for anxious and depressed youth -- Case formulation and treatment planning for anxiety and depression in children and adolescents -- Effectively engaging and collaborating with children and adolescents in cognitive behavioral therapy sessions -- Facilitating homework and generalization of skills to the real world -- Specific CBT techniques -- Managing negative thoughts, part 1: cognitive restructuring and behavioral experiments -- Managing negative thoughts, part 2: positive imagery, self-talk, thought stopping, and thought acceptance -- Changing maladaptive behaviors, part 1: exposure and response prevention -- Changing maladaptive behaviors, part 2: the use of behavioral activation and pleasant events scheduling with depressed children and adolescents -- Managing maladaptive mood and arousal -- Problem-solving skills training -- Social skills training -- Modifying the family environment.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Anxiety in children -- Treatment; Anxiety in adolescence -- Treatment; Depression in children -- Treatment; Depression in adolescence -- Treatment; Cognitive therapy; PSYCHOLOGY -- Clinical Psychology; Anxiety in adolescence -- Treatment; Anxiety in children -- Treatment; Cognitive therapy; Depression in adolescence -- Treatment; Depression in children -- Treatment; Anxiety Disorders -- therapy; Cognitive therapy -- Methods; Child; Adolescent; Evidence-Based Medicine -- methods; Electronic books; Electronic books